Chronological Changes of Viral Shedding in Adult Inpatients With COVID-19 in Wuhan, China. (23rd May 2020) - Huang, Jing-Tao; Ran, Ruo-Xi; Lv, Zhi-Hua; Feng, Li-Na; Ran, Chen-Yang; Tong, Yong-Qing; Li, Dong; Su, Han-Wen; Zhu, Cheng-Liang; Qiu, Shi-Li; Yang, Jie; Xiao, Meng-Yao; et al.
Abstract: Background: In December 2019, the coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) broke out in Wuhan. Epidemiological and clinical characteristics of patients with COVID-19 have been reported, but the relationships between laboratory features and viral load has not been comprehensively described. Methods: Adult inpatients (≥18 years old) with COVID-19 who underwent multiple (≥5 times) nucleic acid tests with nasal and pharyngeal swabs were recruited from Renmin Hospital of Wuhan University, including general patients (n = 70), severe patients (n = 195), and critical patients (n = 43). Laboratory data, demographic data, and clinical data were extracted from electronic medical records. The fitted polynomial curve was used to explore the association between serial viral loads and illness severity. Results: Viral load of SARS-CoV-2 peaked within the first few days (2–4 days) after admission, then decreased rapidly along with virus rebound under treatment. Critical patients had the highest viral loads, in contrast to the general patients showing the lowest viral loads. The viral loads were higher in sputum compared with nasal and pharyngeal swab ( P = .026). The positive rate of respiratory tract samples was significantly higher than that of gastrointestinal tract samples ( P < .001). The SARS-CoV-2 viral load was negatively correlated with portion parameters of blood routine and lymphocyte subsets and was positively associated with laboratory features of cardiovascular system. Conclusions: The serial viral loads of patients revealed whole viral shedding during hospitalization and the resurgence of virus during the treatment, which could be used for early warning of illness severity, thus improve antiviral interventions. Abstract : The serial viral loads of SARS-CoV-2 in patients with COVID-19 revealed viral replication and shedding in different sites during the treatment. The resurgence of SARS-CoV-2 informed that a stricter discharge criterion should be taken.